IDENTIFICATION AND PHYTOCHEMICAL TESTS OF FUNGI MUSHROOMS AND HONEY SPECIALLY BANGKA BELITUNG - Purba, Eva Dewi Rosmawati; Djuria, Rachmawati Felani; Lingga, Rahmad (Universitas Negeri Medan, 2024)
Pelawan Bitter Honey and Pelawan Mushroom are typical Bangka biodiversity found in Central Bangka Regency. The Pelawan mushroom grows in Bangka Belitung Islands Province and generally used as a food ingredient and has the potential to be developed as a source of natural immunomodulator agent. Phenolic compounds are known to have immunomodulatory activities that can improve the immune system. In addition, based on preliminary study, honey was also used by local people to strengthen the immune system. The purpose of this study was to identify the content of active compounds from Pelawan honey and Pelawan mushrooms. This research was an experimental study with several stages of testing including phytochemical screening, Thin Layer Chromatography and Extract Standardization tests. The results showed that based on phytochemical test of Pelawan honey contained flavonoids and alkaloids, while based on the Thin Layer Chromatography (TLC) test contained flavonoids and alkaloids. Phytochemical test of Pelawan mushroom showed the existence of Phenolic and Alkaloids, while based on TLC test containing flavonoids with an average Rf value of 0.56. The standardization of Pelawan mushroom extract produced a total ash content of 28%, drying shrinkage of 40.88 g /mL, specific gravity 0.67 g/mL and water soluble extract content of 59.01% and ethanol soluble extract content of 41.12%. From these results, it can be assumed that the pelawan honey and pelawan mushroom have the potential to be developed as immunomodulatory agent.